1H NMR-based metabolomics and UHPLC-ESI-MS/MS for the investigation of bioactive compounds from Lupinus albus fractions. (February 2021) - Hellal, Khaoula; Mediani, Ahmed; Ismail, Intan Safinar; Tan, Chin Ping; Abas, Faridah
Graphical abstract: Highlights: Metabolite-bioactivity correlation of Lupinus albus fractions were evaluated. Chloroform fraction was identified as bioactive fraction. 35 metabolites were identified from L. albus using 1 H NMR metabolomics. A total of 21 metabolites are tentatively identified using UHPLC-ESI-MS. Abstract: Lupinus albus or white lupine has recently received increase attention for its medicinal values. Several studies have described the hypoglycemic effect of the white lupine, which is known as a food plant with potential value for treatment of diabetes. This study provides useful information for the identification and quantification of compounds in L. albus fractions by proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. In total, 35 metabolites were identified from L. albus fractions. Principal component analysis (PCA) was used as a multivariate projection method for visualizing the different composition of four different fractions. The bioactivities of fractions with different polarity obtained from the extract of L. albus seeds are reported. Among the fractions studied, the chloroform fraction (CF) exhibits a high free radical scavenging (DPPH) and α-glucosidase inhibitory activities with IC50 values of 24.08 and 20.08 μg/mL, respectively. A partial least-squares analyses (PLS) model had been successfully performed to correlate the potential active metabolites with the corresponding biological activities. Metabolites containing proline, caprate, asparagine, lupinoisolone C, hydroxyiso lupalbigenin and some unknown compounds show high correlation with the bioactivities studied. Moreover, the structural identification in the active fraction was supported by ultrahigh-performance-liquid chromatography–electrospray ionization tandem mass spectrometry (UHPLC-ESI-MS/MS) analysis. A total of 21 metabolites were tentatively identified from MS/MS data by comparison with previously reported data. Most of these compounds are isoflavonoids without known biological activity. This information may be useful for developing functional food from L. albus with potential application in the management of diabetes.